2010
DOI: 10.1177/1541204010377748
|View full text |Cite
|
Sign up to set email alerts
|

How Do Families Matter? Age and Gender Differences in Family Influences on Delinquency and Drug Use

Abstract: Parenting practices, age, and gender all influence adolescent delinquency and drug use, but few studies have examined how these factors interact to affect offending. Using data from 18,512 students in Grades 6, 8, 10 and 12, this study found that across grades, parents treated girls and boys differently, but neither sex received preferential treatment for all practices assessed, and younger children reported more positive parenting than older students. Family factors were significantly related to delinquency a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 68 publications
6
52
2
2
Order By: Relevance
“…The relationship between parenting and delinquency was initially conceptualized by Loeber and Stouthamer-Loeber (1986) as involving parental criminality, parental monitoring/discipline, youth attachment to parents, and parental support. Certain parental behaviors were associated with greater youth involvement in delinquency and drug use (Ardelt and Day 2002;Barnes and Farrell 1992;Fagan et al 2011;Herrenkohl et al 2000;Scaramella et al 2002). There is also now a sizeable body of research on the interactional effect that delinquency has on parenting practices (Huh et al 2006;Jang and Smith 1997;Laird et al 2003;Reitz et al 2006;Scaramella et al 2002;Stice and Barrera 1995;Vuchinich, Bank, and Patterson 1992).…”
Section: Parenting and Delinquencymentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between parenting and delinquency was initially conceptualized by Loeber and Stouthamer-Loeber (1986) as involving parental criminality, parental monitoring/discipline, youth attachment to parents, and parental support. Certain parental behaviors were associated with greater youth involvement in delinquency and drug use (Ardelt and Day 2002;Barnes and Farrell 1992;Fagan et al 2011;Herrenkohl et al 2000;Scaramella et al 2002). There is also now a sizeable body of research on the interactional effect that delinquency has on parenting practices (Huh et al 2006;Jang and Smith 1997;Laird et al 2003;Reitz et al 2006;Scaramella et al 2002;Stice and Barrera 1995;Vuchinich, Bank, and Patterson 1992).…”
Section: Parenting and Delinquencymentioning
confidence: 99%
“…Social support includes showing praise and encouragement, along with spending quality time with children (Wright and Cullen 2001). Parents who sustain positive and supportive relationships with their children not only help them learn coping skills, but may steer them away from delinquent activities because youth may not want to jeopardize their positive relationships (Fagan et al 2011). Parental support is a significant predictor of minor delinquency and youth alcohol use, even after accounting for demographic variables, family structure, and parental alcohol abuse (Barnes and Farrell 1992).…”
Section: Parental Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that males and females have different emotional and behavioral tendencies which evolve depending on age and context (Bank, Delamont, & Marshall, 2007). Research in family structure has consistently ignored the significance of gender differentials, but recent research has justified the need to explore family structure and gender jointly so as to understand how family environment shapes adolescent development for males and females (Fagan, Van Horn, Antaramian, & Hawkins, 2011). Gender plays an important role in educational outcomes of young people, and recent studies are documenting a female advantage; however, the process by which gender roles influence the educational outcomes of youth has rarely been studied, especially in Nigeria where preference is still given to males compared with females when it comes to educational opportunities (Kazeem et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…School characteristics that encourage students' involvement and positive interactions have been consistently noted as significant protective factors (Arthur et al, 2002;O'Brien et al, 2013;Wasserman et al, 2003). Previous studies also show the complex and dynamic patterns of youth violence by students' demographics: In general, male and older youth often appear to be at-risk populations who have higher levels of risk factors and lower levels of protective factors leading to increased involvement in violence (Fagan et al, 2011;Fagan et al, 2007;Herrenkohl et al, 2000).…”
mentioning
confidence: 98%